1988
DOI: 10.2527/jas1988.66102524x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Absolute Growth Rate, Relative Growth Rate and Feed Conversion during Postweaning Feedlot Performance Tests

Abstract: Knowledge of the relationships between absolute growth rate (AGR), relative growth rate (RGR) and feed conversion (FCONV) of bulls in postweaning feedlot performance tests can give cattle producers important information for selecting superior sires. Weight gain and FCONV data that were collected during 16 yr were analyzed from 393 Angus and 340 Hereford bulls by 26 and 27 sires, respectively, that were individually fed in 140-d tests. Sire variance and covariance components were used to obtain heritability (h2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 5 publications
4
12
0
1
Order By: Relevance
“…The favorable (negative) genetic correlations between FCR and growth traits observed in our study were in agreement with the estimates by Brown (1988), Fan et al (1995) and Arthur et al (2001a). The high negative genetic relationship between ADG and FCR (脌 0.84 and 脌 0.74 for Angus and Hereford breed, respectively) has been reported by Brown (1988) and (脌 0.62 and 脌 0.57 for Angus and Hereford breed, respectively) by Fan et al (1995).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The favorable (negative) genetic correlations between FCR and growth traits observed in our study were in agreement with the estimates by Brown (1988), Fan et al (1995) and Arthur et al (2001a). The high negative genetic relationship between ADG and FCR (脌 0.84 and 脌 0.74 for Angus and Hereford breed, respectively) has been reported by Brown (1988) and (脌 0.62 and 脌 0.57 for Angus and Hereford breed, respectively) by Fan et al (1995).…”
Section: Discussionsupporting
confidence: 94%
“…The high negative genetic relationship between ADG and FCR (脌 0.84 and 脌 0.74 for Angus and Hereford breed, respectively) has been reported by Brown (1988) and (脌 0.62 and 脌 0.57 for Angus and Hereford breed, respectively) by Fan et al (1995). Arthur et al (2001a) found the high negative genetic correlation (脌 0.62) between these traits for Angus breed.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, both MWT and ADG were phenotypically independent of RFI. The favourable (negative) genetic correlations of FCR with growth traits observed in the present study were in agreement with the estimates by Brown (1988); Fan et al (1995) and Arthur et al (2001). Weighted mean values for genetic and phenotypic correlations noted in a review by Koots et al (1994b) were )0.67 and )0.64 for FCR with ADG, respectively, and the corresponding correlations were )0.60 and )0.46 for FCR with yearling weight, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Average initial test ages in these data allow bulls to be at least 12 mo of age by d 112 of test. There is a positive relationship between body condition and scrotal circumference (Chewning et al, 1988). Coulter and Foote (1977) reported that cumference measurements 2 to 3 cm greater than bulls in good body condition.…”
Section: Results and Dlscusslonmentioning
confidence: 97%
“…Coulter and Foote (1977) reported that cumference measurements 2 to 3 cm greater than bulls in good body condition. Chewning et al (1988) reported least squares estimates for the effects of initial test weight, backfat, and average daily gain on scrotal c i r d e rence. These estimates could be used to adjust scrotal circumference measurements for these effects, Scrotal circumference has been shown to be a more accurate indicator of puberty in bulls than either age or weight, regardless of breed or breed cross (Lunstra, 1982).…”
Section: Results and Dlscusslonmentioning
confidence: 99%